Anodic Formation of Thick Anatase TiO2 Mesosponge Layers for High-Efficiency Photocatalysis - Lee, Kiyoung; Kim, Dam-Hee; Roy, Poulomi; Paramasivam, Indhumati; Birajdar, Balaji; Spiecker, Erdmann; Schmuki, Patrik (Journal of the American Chemical Society, 2010)
We report a process for the flabrication of an anatase TiO2 mesosponge (TMS) layer by an optimized Ti anodization process in a hot glycerol electrolyte followed by a suitable etching process. Such layers can easily be grown to > 10 mu m thickness and have regular channels and structural features in the 5-20 nm range. The layers show high photocatalytic activity and are mechanically very robust. The layers therefore open new pathways to the wide field of TiO2(anatase) applications.

Direct in situ transmission electron microscopy observation of Al push up during early stages of the Al-induced layer exchange - Birajdar, Balaji; Antesberger, T.; Butz, Benjamin; Stutzmann, Martin; Spiecker, Erdmann (Scripta Materialia, 2012)
The mechanism of Al transport during Al-induced layer exchange and crystallization of amorphous Si (a-Si) has been investigated by in situ and analytical transmission electron microscopy. Significant grain boundary realignment and coarsening of Al grains close to the Si crystallization growth front as well as push up of excess Al into the a-Si layer at distances even a few micrometers away from the crystallization front were observed. Stress-mediated diffusion of Al is postulated to explain the experimental observations. (C) 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Thin films; Solar cells; Crystallization; Analytical electron microscopy; Diffusion

Epitaxial upward transport of Al at the beginning of the Al-induced layer exchange process - Birajdar, Balaji; Antesberger, Tobias; Stutzmann, Martin; Spiecker, Erdmann (Physica Status Solidi-Rapid Research Letters, 2011)
Al-induced layer exchange (ALILE) and crystallization in a stack of amorphous Si (a-Si, 100 nm)/Al (50 nm)/quartz substrate, annealed at 450 degrees C, have been investigated at different length scales by optical microscopy as well as analytical scanning and transmission electron microscopy. Significant lateral and vertical redistribution of Al was observed, yielding Al deficient dendritic cell centers surrounded by an about 10 mu m wide Al excess zone containing epitaxial islands of "pushed-up" Al whose number density and size decreases with increasing distance from the cell boundary. This new finding is likely to be a key step forward in the understanding of the complex redistribution of Al and Si during the ALILE process. (C) 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: thin films; solar cells; crystallization; electron microscopy

Formation of a Non-Thickness-Limited Titanium Dioxide Mesosponge and its Use in Dye-Sensitized Solar Cells - Kim, Dam-Hee; Lee, Kiyoung; Roy, Poulomi; Birajdar, Balaji; Spiecker, Erdmann; Schmuki, Patrik (Angewandte Chemie International Edition, 2009)
Etch a sketch: Robust TiO_2 mesoporous layers can be fabricated on Ti surfaces by a combination of non-thickness-limited anodization and selective etching. Layers more than 50 extgreekmm thick with highly regular feature and pore sizes in the range 5–10 nm can be produced (see picture, FTO=fluorine doped tin oxide). The layers are highly flexible, well-adhered, and can be used directly after appropriate annealing in efficient dye-sensitized solar cells.
Keywords: dyes/pigments; mesoporous materials; solar cells; titanates; titanium

In Situ and Analytical Transmission Electron Microscopy - Birajdar, Balaji; Spiecker, Erdmann (Imaging & Microscopy, 2012)
In situ and analytical transmission electron microscopy (TEM) has been used to investigate the mechanism of material transport during Al-induced layer exchange (ALILE) and crystallization of amorphous Si (a-Si). Significant lateral and vertical redistribution of Al was observed, yielding Al deficient dendritic cell centers surrounded by an about 10 µm wide Al excess zone containing epitaxial islands of -upAl whose number density and size decreases with increasing distance from the cell boundary.
EAM Import::2019-03-13

Investigation of the size-property relationship in CuInS2 quantum dots - Akdas, Tugce; Walter, Johannes; Segets, Doris; Distaso, Monica; Winter, Benjamin; Birajdar, Balaji; Spiecker, Erdmann; Peukert, Wolfgang (Nanoscale, 2015)
In this work we investigated fundamental properties of CuInS2 quantum dots in dependence of the particle size distribution (PSD). Size-selective precipitation (SSP) with acetone as poor solvent was performed as an adequate post-processing step. Our results provide deep insight into the correlation between particle size and various optical characteristics as bandgap energy, absorption and emission features and the broadness of the emission signal. These structure-property relationships are only achieved due to the unique combination of different analytical techniques. Our study reveals that the removal of 10 wt% of smallest particles from the feed results in an enhancement of the emission signal. This improvement is ascribed to a decreased quenching of the emission in larger particles. Our results reveal the impact of PSDs on the properties and the performance of an ensemble of multicomponent QDs and anticipate the high potential of controlling PSDs by well-developed post-processing.

The effects of post-processing on the surface and the optical properties of copper indium sulfide quantum dots - Akdas, Tugce; Distaso, Monica; Kuhri, Susanne; Winter, Benjamin; Birajdar, Balaji; Spiecker, Erdmann; Guldi, Dirk Michael; Peukert, Wolfgang (Advances in Colloid and Interface Science, 2015)
In the current contribution we report on investigations regarding the surface of CuInS2 quantum dots and on different strategies to control the amount of surface ligands in a post-processing step. In particular, the reactivity of the organic components, that is, 1-dodecanthiol and 1-octadecene as ligand and solvent, respectively, during nanocrystal formation was studied. A new method to remove residuals from the reaction mixture and to detach excess organics from the surface of the nanocrystals is reported. Our new method, which is based on the utilization of acids, is compared with standard purification procedures by means of thermogravimetric analysis (TGA) with particular focus on its efficiency to remove organics. As a complement, the surface chemistry is analyzed by nuclear magnetic resonance spectroscopy (NMR) to shed light on the nature of the organic components still present after purification. Further analysis of the product by inductively coupled plasma optical emission spectroscopy (ICP-OES) is performed to verify the influence of the new purification method on surface composition and properties. Moreover, steady state and time resolved spectroscopies give insights into excitonic behavior as well as recombination processes. Finally, the new method is optimized for the purification of CuInS2-ZnS nanocrystals, which show enhanced optical properties.